2013
DOI: 10.11606/issn.2317-0190.v20i1a103753
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Fugl-Meyer Assessment (FMA) and the Wolf Motor Function Test (WMFT) in the recovery of upper limb function in patients after chronic stroke: a literature review

Abstract: It is estimated that 45-75% of chronic adult stroke patients have difficulty in using the hemiparetic upper limb (MS) in their daily life activities (DLAs). Functional scales are used in the practice of rehabilitation, in the search for diagnoses and prognoses, and in evaluating response to treatment. The Wolf Motor Function Test (WMFT) and Fugl-Meyer Assessment (FMA) scales are the instruments most commonly mentioned in the literature. Objective: The aim of this study was to review the use of the WMFT and FMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similar to previous studies, our results of FMA and WMFT tests confirmed the improvement of all patients' motor ability and recovery after the rehabilitation process [ 6 , 11 ]. The fMRI findings were also consistent with the improvements, where we observed an increase in motor activation in all ipsilesional motor areas (except in BA3aL region of a patient).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies, our results of FMA and WMFT tests confirmed the improvement of all patients' motor ability and recovery after the rehabilitation process [ 6 , 11 ]. The fMRI findings were also consistent with the improvements, where we observed an increase in motor activation in all ipsilesional motor areas (except in BA3aL region of a patient).…”
Section: Discussionsupporting
confidence: 91%
“…To assess the functional improvement in stroke patients, studies have suggested two impairment indices, i.e., Fugl-Meyer assessment-upper extremity (FMA-UE) and Wolf motor function test (WMFT) [ 6 ]. The FMA is a stroke-specific performance-based impairment index, designed to assess motor functioning, balance, sensation, and joint functioning in patients with poststroke hemiplegia.…”
Section: Introductionmentioning
confidence: 99%